2013
DOI: 10.1093/intqhc/mzt018
|View full text |Cite
|
Sign up to set email alerts
|

Accreditation of hospitals in Lebanon: is it a worthy investment?

Abstract: The financial burden of accreditation on hospitals has to be factored in the decision of its adoption at a national level, especially in developing countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
54
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(59 citation statements)
references
References 8 publications
3
54
0
2
Order By: Relevance
“…As observed in a research results, most responding hospitals considered accreditation as a worthy investment due to its effect on enhanced quality and safety culture (SALEH et al, 2013). In another study, accreditation was actually considered the starting step in the process to reach excellence in hospitals (ABDALLAH et al, 2013).…”
Section: Organizational Impactsmentioning
confidence: 97%
See 2 more Smart Citations
“…As observed in a research results, most responding hospitals considered accreditation as a worthy investment due to its effect on enhanced quality and safety culture (SALEH et al, 2013). In another study, accreditation was actually considered the starting step in the process to reach excellence in hospitals (ABDALLAH et al, 2013).…”
Section: Organizational Impactsmentioning
confidence: 97%
“…The impact of accreditation programs on health service organizations and units were examined in 27 studies CASTLE, 2012b;YU, 2012;GUINDO et al, 2012;ABDALLAH et al, 2013;PRONOVOST et al, 2013;SALEH et al, 2013;DAY et al, 2013;ABOU ELNOUR et al, 2014;LEE, 2014;MARONE et al, 2014;MARSHALL, 2014;MBAH et al, 2014;MOHAMMADI;MATIN;RIAHI, 2014;PARTHASARATHY;SUBRAMANIAN;QUAN, 2014;SAGHATCHIAN et al, 2014;SHAW et al, 2014;SONG;LI;ZHOU, 2014;MORAN, 2014;YILDIZ;KAYA, 2014;CARMAN;TIMSINA;SCUTCHFIELD, 2014;EL-JARDALI et al, 2014;GREENFIELD et al, 2014c;WENSING, 2015;RAJAN et al, 2015;ANDIRIC;MASSAMBU, 2015;SISAY et al, 2015;CHEN et al, 2015), including continuous quality improvement, the quality of care and safety of organizational cultures, compliance with external programs guidelines, standardization of care processes, and performance management systems. As observed in a research results, most responding hospitals considered accreditation as a worthy investment due to its effect on enhanced quality and safety culture (SALEH et al, 2013).…”
Section: Organizational Impactsmentioning
confidence: 99%
See 1 more Smart Citation
“…Note taking was used to be able to document the whole interview process since some of the respondents did not approve to be audio-taped. * Small: Number of beds less than or equal to 100; Large: Number of beds more than 100 [7]. ** Table 2: Summary of the questions that were addressed linked to the study objectives.…”
Section: Data Collectionmentioning
confidence: 99%
“…For example, some hospitals are constructed in a manner that does not respect the positive flow of the waste collection traffic; thus, increasing the possibility of infection transmission. A research study conducted by Saleh et al [7] explores the views of stakeholders in Lebanese hospitals on the expenses of accreditation revealed that about 77% consider infrastructure maintenance a burden. Hospitals in developing countries may be disadvantaged because compliance may require massive investments beyond available resources and capabilities.…”
Section: Challenges Of Implementing Environmental Management Practicesmentioning
confidence: 99%